Temperature-Properties Relationships of Martensitic Stainless Steel for Improved Utilization in Surgical Tools - Ahmed, Ibrar; Badar-ud-Din Soomro; Muhammad Irfan; Noor Faraz Khan; Muhammad Bilal Afzal; Junaid Israr; Ambreen Saddozai; Muhammad Yousif (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Sintering temperature and environment plays a very important role in strengthening powder particles of compacting surgical parts by cold powder metallurgy technique. Powder metallurgy is a process of producing components/tools by compacting finely metallic or nonmetallic powders. Generally, in the last decade, these tools were produced by conventional casting techniques but now first time in Pakistan this technique is introduced to develop surgical tools/parts. In this study, the effect of sintering behavior by varying temperatures and environments was studied. The AISI 420 Stainless steel compacted surgical parts (Scalpel and scissor) were sintered at 1000 °C to 1300 °C for 30 minutes in a vacuum and an inert environment in the presence of Argon. The compact density, microstructure and mechanical properties were studied. Microstructural characteristics like porosity, and crystalline size were studied by optical microscope. The hardness values and density of the final parts were also measured through the Rockwell hardness machine and by the Archimedes principle. Decreasing the porosity in the final parts will increase the mechanical properties of sintered parts. Adopting the present process for the development of surgical tools after further refining, the process will prove beneficial in the cost-effectiveness, time and energy saving of the present product.